تأثير البعد الايديولولوجي على مواقف الاحزاب السياسية في الجزائر - كياتي, عبد القادر; مرغني, بلقاسم (My University, 2023)
.تهدف هذه الدراسة إلى تسليط الضوء على الدور الذي تلعبه الأيديولوجيا في المواقف السياسية والاجتماعية والاقتصادية للأحزاب السياسية في الجزائر، وكيف نشأت هذه الأفكار والمعتقدات، وكذلك الأسباب التي يمكن أن تجعل الحزب يتخلى عن أيديولوجياته، كما حاولنا وضع رؤية للخريطة الحزبية في الجزائر تحت منظور أيديولوجي. من أجل تحقيق أهداف دراستنا ، تم استخدام النهج التاريخي والنهج المؤسسي ، وكذلك التطبيق المقارن.This study aims to highlight the role played by ideology in the political, social and economic positions of political parties in Algeria, and how these ideas and beliefs arose, as well as the reasons that can make the party abandon its ideologies, as well as we tried to develop a vision of the partisan map in Algeria under the perspective of ideology. In order to achieve the objectives of our study, the historical approach and the institutional approach were used, as well as the comparative approach. The second chapter, which is the procedural chapter of the study, included many partisan positions and we compared them with the ideologies of each party so that we could know the background of these positions. Our study dealt with the most important political parties in Algeria. With its various orientations, we have concluded that parties generally depend on their ideologies in political and other positions, and they can also abandon them in some cases.
مذكرة ماستر
Keywords: الأحزاب, الأحزاب السياسية, الأيديولوجية, المعتقدات, الأفكار; parties, political parties, ideology, beliefs, ideas